The Lost Town of Yibaba: Royal Residence and Regional Capital (ca. 1612- ca.1800) - Eskezia, Geremew (Ethiopian Journal of Social Sciences, 2021)
Yibaba served as the capital of a region to the south of Lake Tana called Mecha province, and, as a royal residence of Gondarine emperors since the early 17th century, provided the same function as the town of Aringo in Begemdir. Yibaba also played a significant role in the Gondarine politics and the power struggles of the early decades of the Zemene Mesafint (the era of warlords). Although the town was an important political center for centuries, there is no as such focused and significant historical study that has been made on Yibaba. Therefore, this paper provides a short historical account of the lost town of Yibaba, including the office of Yibaba Azazh, the province of Mecha and the political developments and relations of the town with the kings in Gondar. To this end, a range of sources is used including oral, published and unpublished sources